Mobile game development with augmented reality for Ipoh Cave attractions - Tan, Jun Jie (2022)

(untitled)
A lot of cave attractions located in Ipoh, Perak are yet to be discovered by foreign tourists. These cave attractions are like hidden gems awaiting tourists from other countries to discover them. In this project, a AR mobile game will be developed to tackle the problem mentioned just now. The mobile game to be develop will be able to integrate into those cave attractions in Ipoh, and thus enhance the travel experience of tourists who visit to those cave attractions. Not only that, the mobile game to be developed can also educate tourists about the information or history of cave attractions in an interesting way, so that tourists won’t felt bored when they are exposed to these information. This indirectly also spread the history and information of the cave attractions to more and more tourists. The mobile game will also use Augmented Reality(AR) technology that we have now to further enhance the tourists travel experience, because AR games have the capabilities to immerse into a fictional worlds and impact events within that fictional world.